2021
DOI: 10.1186/s12903-021-01649-2
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of gypsum casts obtained from the disinfected extended-pour alginate impressions through prolonged storage times

Abstract: Background Manufacturers of the extended-pour alginates claimed their dimensional stability through prolonged storage. No data confirmed the ability of these materials to maintain their dimensions and the reproduced oral details following their chemical disinfection. Therefore, this study evaluated the dimensional stability and surface detail reproduction of gypsum casts obtained from disinfected extended-pour alginate impressions through different storage time intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 44 publications
0
14
0
4
Order By: Relevance
“…As a rule of thumb, the concentration value will be greatly influenced by the molecular weight of the alginate. The higher the molecular weight, the higher the viscosity [2,14]. Previously published studies reported that the viscosity of dental impression material can be increased if the extraction of potassium alginate is carried out using freshly harvested seaweed [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a rule of thumb, the concentration value will be greatly influenced by the molecular weight of the alginate. The higher the molecular weight, the higher the viscosity [2,14]. Previously published studies reported that the viscosity of dental impression material can be increased if the extraction of potassium alginate is carried out using freshly harvested seaweed [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Impression procedure is one of the most crucial steps in producing successful dental appliances, indirect restorations, and prostheses particularly in the orthodontic and prosthodontic field [1][2][3]. The impression material is especially beneficial for molding serrated jaws or partial edentulous jaws to obtain a dental cast for master study [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations